Hollow biomorphic Al2O3 fibers produced from sisal - Andrade Júnior, Tarcísio Eloi de (2021)
Al2O3 fibers with a hollow morphology were produced by Al-vapor infiltration-reaction and subsequent oxidation from pyrolysed fibers of natural sisal. Following pyrolysis, the bio-fiber template was reacted with gaseous Al at 1,400 C–1,600 C in vacuum to form Al4C3. After an oxidation/sintering process at 1,550 C, the biomorphic Al4C3 fibers were fully converted into Al2O3, maintaining the microstructural features of the native sisal. Phase and microstructural characterization during processing were evaluated by high temperature X-ray diffractometry and scanning electron microscopy, respectively. Thermo-analyses were performed in the Al4C3 samples in order to estimate the reactions and the weight change during the oxidation step